Data science analytics and applications : first International Conference, DaSAA 2017, Chennai, India, January 4-6, 2017, Revised selected papers /: first International Conference, DaSAA 2017, Chennai, India, January 4-6, 2017, Revised selected papers. (2018) - Unknown
No abstract available